2015
DOI: 10.1007/s10936-015-9372-4
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity in L1 Attrition: Differential Object Marking in Spanish Near-Native Speakers of English

Abstract: Previous research has shown L1 attrition to be restricted to structures at the interfaces between syntax and pragmatics, but not to occur with syntactic properties that do not involve such interfaces ('Interface Hypothesis', Sorace and Filiaci 2006). The present study tested possible L1 attrition effects on a syntax-semantics interface structure (Differential Object Marking using the Spanish personal preposition) as well as the effects of recent L1 re-exposure on the potential attrition of these structures, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 37 publications
1
18
1
Order By: Relevance
“…Selectivity phenomenon is, in fact, not new to L1 attrition research. Previous research demonstrated external interface‐governed structures, such as distribution of subject pronouns and differential object marking as potential loci for erosion (Chamorro, Sturt, & Sorace, ), which is often framed within the interface hypothesis as formulated by Sorace (). There is also evidence showing that structures that are not in competition between the L1 and L2 may be fully retained (Gürel, ).…”
Section: Discussionmentioning
confidence: 99%
“…Selectivity phenomenon is, in fact, not new to L1 attrition research. Previous research demonstrated external interface‐governed structures, such as distribution of subject pronouns and differential object marking as potential loci for erosion (Chamorro, Sturt, & Sorace, ), which is often framed within the interface hypothesis as formulated by Sorace (). There is also evidence showing that structures that are not in competition between the L1 and L2 may be fully retained (Gürel, ).…”
Section: Discussionmentioning
confidence: 99%
“…The same pattern was also found for L2 speakers of Italian (same language combination) and the attested difficulties have been termed residual optionality for L2 speakers and emerging optionality for speakers with L1 attrition. This led Sorace to the postulation of the Interface Hypothesis as a unified framework of bilingualism, treating L2 acquisition, bilingual L1 acquisition and L1 attrition alike ( Sorace and Filiaci, 2006 and related work). According to this hypothesis, phenomena that are purely syntactic (at an internal interface) are impervious to attrition and acquirable in L2, while external interface phenomena might lead to persistent deficits in both groups of speakers.…”
Section: Linguistic Backgroundmentioning
confidence: 99%
“…As with L2 effects, the corresponding evidence is quite inconsistent. On the one hand, several studies have reported higher levels of attrition in participants who had a progressively weaker contact with their L1 (de Bot et al, 1991;Köpke, 1999, Isurin, 2007Opitz, 2013;Chamorro et al, 2016b;Bergman et al, 2016;Kasparian et al, 2017;Schmid and Yilmaz, 2018;Karayayla and Schmid, 2019) supporting the idea that the amount of L1 contact predicts the severity of attrition. Note that these studies are quite heterogeneous in their use of experimental methodologies including EEG (Kasparian et al, 2017), eye-tracking (Chamorro et al, 2016b), and behavioral methods.…”
Section: Exposure To L1: Quantity and Qualitymentioning
confidence: 99%
“…On the one hand, several studies have reported higher levels of attrition in participants who had a progressively weaker contact with their L1 (de Bot et al, 1991;Köpke, 1999, Isurin, 2007Opitz, 2013;Chamorro et al, 2016b;Bergman et al, 2016;Kasparian et al, 2017;Schmid and Yilmaz, 2018;Karayayla and Schmid, 2019) supporting the idea that the amount of L1 contact predicts the severity of attrition. Note that these studies are quite heterogeneous in their use of experimental methodologies including EEG (Kasparian et al, 2017), eye-tracking (Chamorro et al, 2016b), and behavioral methods. Moreover, these findings are corroborated by the research investigating attrition in adopted children who show fast, almost absolute, and irreversible attrition of their native language due to the total severance from L1 use (Isurin, 2000;Nicoladis and Grabois, 2002;Pallier et al, 2003;Ventureyra et al, 2004).…”
Section: Exposure To L1: Quantity and Qualitymentioning
confidence: 99%